Increased glymphatic system activity in migraine chronification by diffusion tensor image analysis along the perivascular space - Zhang, Xue; Wang, Wei; Bai, Xiaoyan; Zhang, Xueyan; Yuan, Ziyu; Jiao, Bingjie; Zhang, Yingkui; Li, Zhiye; Zhang, Peng; Tang, Hefei; Zhang, Yaqing; Yu, Xueying; et al. (Journal of headache and pain, 2023)
Background Preliminary evidence suggests that several headache disorders may be associated with glymphatic dysfunction. However, no studies have been conducted to examine the glymphatic activity in migraine chronification. Purposes To investigate the glymphatic activity of migraine chronification in patients with episodic migraine (EM) and chronic migraine (CM) using the diffusion tensor image analysis along the perivascular space (DTI-ALPS) method. Methods In this cross-sectional study, patients with EM, CM, and healthy controls (HCs) were included. All participants underwent a standard brain magnetic resonance imaging (MRI) examination. Bilateral DTI-ALPS indexes were calculated for all participants and compared among EM, CM, and HC groups. Correlations between the DTI-ALPS index and clinical characteristics were analyzed. Results A total of 32 patients with EM, 24 patients with CM, and 41 age- and sex-matched HCs were included in the analysis. Significant differences were found in the right DTI-ALPS index among the three groups ( p = 0.011), with CM showing significantly higher values than EM ( p = 0.033) and HCs ( p = 0.015). The right DTI-ALPS index of CM group was significantly higher than the left DTI-ALPS index ( p = 0.005). And the headache intensity was correlated to DTI-ALPS index both in the left hemisphere ( r = 0.371, p = 0.011) and in the right hemisphere ( r = 0.307, p = 0.038), but there were no correlations after Bonferroni correction. Conclusions Glymphatic system activity is shown to be increased instead of impaired during migraine chronification. The mechanism behind this observation suggests that increased glymphatic activity is more likely to be a concomitant phenomenon of altered vascular reactivity associated with migraine pathophysiology rather than a risk factor of migraine chronification.